2018
DOI: 10.1016/j.ptsp.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the reliability of a novel battery of range of motion tests to enable evidence-based classification in Para Swimming

Abstract: The large majority of ROM tests included in this novel battery were reliable both within and between examiners in non-disabled participants. The tests were found to differentiate between non-disabled participants and Para swimmers with hypertonia or impaired muscle power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Studies in Para swimming have identified objective measures of impairment and established their relationship with swimming performance, 4,6‐8 established the impact of eligible types of impairment on sport‐specific measures of swimming performance to guide classification test protocols, 9‐11 and established the impact of impairment on swimming performance to guide revisions in classification structures 12,13 . However, these cross‐sectional studies do not provide an understanding on how measures of impairment, determinants of swimming performance, or the impairment‐performance relationship vary at different stages of athletic development.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Para swimming have identified objective measures of impairment and established their relationship with swimming performance, 4,6‐8 established the impact of eligible types of impairment on sport‐specific measures of swimming performance to guide classification test protocols, 9‐11 and established the impact of impairment on swimming performance to guide revisions in classification structures 12,13 . However, these cross‐sectional studies do not provide an understanding on how measures of impairment, determinants of swimming performance, or the impairment‐performance relationship vary at different stages of athletic development.…”
Section: Introductionmentioning
confidence: 99%
“…For these swimmers, it is possible that impairments in motor coordination or range of movement predispose them to increased form drag or limits their ability to minimise the disturbance of the water during the swim stroke. 24,25 The combination of objective measures of propulsion and drag may better explain the variance in swim performance for Para swimmers with hypertonia and impaired muscle power.…”
Section: Discussionmentioning
confidence: 99%
“…Payton et al [ 70 ] found higher active and passive drag in para-swimmers with central motor and neuromuscular impairments when compared to able-bodied swimmers. Impairments in motor coordination or ROM predispose athletes to increased form drag, with para-swimmers exhibiting significantly reduced ROM compared to their able-bodied peers [ 71 ]. Unique head positions and postures may also affect the streamline position and thus increase form drag.…”
Section: Horizontalmentioning
confidence: 99%